Transition of diesel spray to a supercritical state under engine conditions - Wensing, Michael; Vogel, Thomas; Goetz, Gudrun (International Journal of Engine Research, 2016)
Process operating conditions of modern internal combustion engines can exceed the thermodynamic critical point of an injected liquid fuel. This raises the question of whether the fuel, or at least some of its components, transition to a supercritical state, even in the presence of an ambient gas. Further investigation is required for a better understanding of heat and mass transfer during the process of fuel injection in diesel engines. This article investigates the phase behavior of fuels and their components under supercritical conditions or when injected into such. After a brief review of the current state of research on the topic, we present our study of the phase behavior of three single-component liquids (n-heptane, n-dodecane, n-hexadecane) and their binary mixtures under supercritical conditions in a nitrogen environment using equations of state. In first experiments, these liquids along with a diesel fuel were successfully transitioned to supercritical states by applying engine-relevant but steady state conditions inside a high-pressure, high-temperature constant volume chamber. No influence of the ambient nitrogen on the phase behavior of the examined fluids was found. For further investigation, multicomponent fuels were injected into the chamber in a transient injection process and at typical engine-relevant time scales using a production-type diesel injector. The fuel sprays were examined with Mie scattering, laser-induced fluorescence, and shadowgraphic imaging. The information obtained confirms the presence of a supercritical state and a transcritical phase change. Areas of high density with pronounced fluctuations were visible. The theoretical review in combination with the results obtained from the experiments indicate that fuel injected under the high-pressure and high-temperature conditions, that are present in modern diesel engines at higher loads, does not evaporate but rather shows transition to a supercritical state with a disappearing phase border, but without boiling or changing density.
Created from Fastlane, Scopus look-up
Keywords: critical point; diesel; injection; Supercritical condition; transcritical process